1994
DOI: 10.1006/cbir.1994.1101
|View full text |Cite
|
Sign up to set email alerts
|

Human hypertensive placenta contains an increased amount of Na, K‐ATPase with higher affinity for cardiac glycosides

Abstract: Placentas of women suffering from pregnancy-induced hypertension (PIH) were found to contain a greater amount of Na,K-ATPase molecules, estimated from anthroyl ouabain binding, than normotensive individuals. Both the microsomal fraction of placental cells and purified Na,K-ATPase showed an increased affinity for the specific inhibitor ouabain which, in the case of the microsomes, bound with a dissociation constant of 0.9 nM as compared with 3.4 nM in the controls. Likewise, the dissociation constant of the oua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
(8 reference statements)
1
7
0
Order By: Relevance
“…Observations of the antihypertensive activity of Digibind in preeclampsia agree with the results of studies demonstrating that Digibind produces vasorelaxation in isolated perfused preeclamptic placentae [16]. Moreover, it has also been observed that the Na/K-ATPase from preeclamptic placentae exhibited heightened sensitivity to CTS [21]. The mechanism underlying the antihypertensive effects of Digibind is based on the cross-reactivity with endogenous CTS; this is illustrated by several observations including the restoration of erythrocyte Na/K-ATPase activity by Digibind ex vivo [13,14] and the reduction in plasma Na/K-ATPase inhibitory activity following Digibind infusion [22].…”
Section: Discussionsupporting
confidence: 80%
“…Observations of the antihypertensive activity of Digibind in preeclampsia agree with the results of studies demonstrating that Digibind produces vasorelaxation in isolated perfused preeclamptic placentae [16]. Moreover, it has also been observed that the Na/K-ATPase from preeclamptic placentae exhibited heightened sensitivity to CTS [21]. The mechanism underlying the antihypertensive effects of Digibind is based on the cross-reactivity with endogenous CTS; this is illustrated by several observations including the restoration of erythrocyte Na/K-ATPase activity by Digibind ex vivo [13,14] and the reduction in plasma Na/K-ATPase inhibitory activity following Digibind infusion [22].…”
Section: Discussionsupporting
confidence: 80%
“…In preeclampsia however, plasma and placental levels of CTS, and especially MBG, become substantially elevated and associate with heightened arterial pressure and inhibition of erythrocyte Na/K-ATPase (57,13). Moreover, in PE placental vascular bed exhibits heightened sensitivity to CTS-induced vasoconstriction (25). Recent evidence, however, indicates that the contribution of CTS to PE is not limited to only vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study remains prospective, and all the different aspects of this regulation need to be investigated in the future, including the precise regulatory mechanisms involved, as well as the time course of recorded changes during pregnancy and the effect of the endogenous analogue of ouabain. At the same time, it is noteworthy that in hypertensive pregnancies, the presence of a greater number of Na + –K + ‐ATPase molecules (Amler et al 1994 a , b ) suggests a lack of decrease in the sodium pump proteins (Graves et al 1995; Martinka et al 1996; Lopatin et al 1999; Fedorova et al 2005). In addition, Na + –K + ‐ATPase is known to be regulated by angiotensin and aldosterone, hormones that are increased in normal pregnancy, but blunted in pregnancy‐induced hypertension (Mihailidou et al 2000).…”
Section: Discussionmentioning
confidence: 99%